Endobronchial Valve-Induced Pneumatocele: A Case Report - Skowasch, D.; Pizarro, C.; Valipour, A.; Wilhelm, K. E.; Thomas, D.; Nickenig, G. (Pneumologie, 2013)
We report a 75-year old female patient with advanced emphysema. After endoscopic lung volume reduction with endobronchial valves (EBV), a huge pneumatocele has occured and resolved spontaneously within a few weeks. Albeit rare, pneumatoceles should be considered in patients with relapsing dyspnoe after EBV treatment.